Some cross-country evidence on information rigidity in inflation forecasts - Fazlul Miah; Omar Al-Titi; Abdoul Wane (Cogent Economics & Finance, 2023)
The study investigates the existence and extent of information rigidity in inflation forecasts among 25 developed and 18 developing economies during 2002-2017 period utilizing a survey data set never explored before on this issue. In general, the study finds some evidence of information rigidity. Rigidity is present during the recession period of global financial crisis of 2007 for both the developed and the developing countries alike, and we find weak evidence of information gathering picking up during the recession period. We also find that forecast revisions depend on both own country and cross-country lagged revisions. Therefore, one source of information rigidity is not to incorporate overseas events in forecast revisions quickly and completely.
Keywords: C53; D83; D84; E13; E31; E37; 330; cross-country forecasts; forecast efficiency; forecast smoothing; inflation forecasts; Information rigidity